Left-handed Dental Students - Silva, Maria Aparecida; Souza-Rodrigues, Renata Duarte; Lashowisk, Karina; Oda, Margarete; Vieira, Glauco Fioranelli (Brazilian Dental Science, 2013)
Objectives: to evaluate the frequency of left-handed students and to investigate their difficulties in Operative & Restorative Dentistry, first preclinical discipline of the School of Dentistry, University of São Paulo. Materials and methods: 82 students from both genders participated, who were attending the second year of the course, to whom were applied the Edinburgh Handedness Inventory measurements and a questionnaire about the difficulties encountered by lefty students. Results: in the study sample, we found 6 left-handed students (7%). The greater difficulty reported by them during their laboratorial practice was working in the quadrants on the right side of the manikin’s mouth. Conclusion: therefore, it is clear that Dentistry Schools should be aware of this minority, with regard to the material and equipment availability for lefties, as well as recognition of their difficulties and to orient them to obtain the best performance with minimum discomfort.